Molecular Epidemiology and Therapeutic Potential of Persian Shallot (Allium ascalonicum L.) in the Management of Methicillin Resistant Staphylococcus Aureus Infection - Ghaznavi Rad, Ehsanollah (2010)
Methicillin-resistant Staphylococcus aureus (MRSA) is an established human pathogen that causes both health care-associated (HA) and community-acquired (CA) infections. It has been shown that MRSA strains evolved from the acquisition of staphylococcal cassette chromosome mec (SCCmec) element carrying the mecA gene, which is responsible for methicillin resistance. Increased emergence of multidrug resistance among MRSA strains has become a major concern in the hospital environment, as it invokes a tremendous financial burden and enhanced morbidity and mortality due to hard-to-treat systemic infections. MRSA was introduced into Malaysian hospital in the early 1970s; however the incidence rate has increased to more than 20% during the last few years. The efficient management of MRSA infection in any country relies on correct diagnosis,understanding its antimicrobial resistance profile, epidemiology, transmission routes, appropriate therapeutics and the appropriate infection control measurements. To achieve the goal of establishing baseline dataset for local clinical MRSA strains, Hospital Kuala Lumpur was focused in this study. A one year study from September 2007 to August 2008 was carried out on 389 isolates, a statistically calculated sample size. The prevalence of MRSA was found to be 44.1% and significantly higher in the patients of Indian ethnicity (P < 0.001). Since the first step in any infection management is the correct diagnosis of etiological agents, in the current study a novel 9-valent multiplex PCR (MPCR) plus two primer pairs for S. aureus identification and detection of methicillin resistance was optimized with established primers by using reference strains. All 389 clinical MRSA isolates from Malaysia and 18 European isolates from the HARMONY collection harboring different SCCmec types were correctly characterized by the novel MPCR assay. Therefore the MPCR assay optimized here in could type any MRSA globally. It is understood from the phenotypic antibiotic susceptibility testing that many of the local MRSA strains were multi drug resistant with different profiles indicating that more than one clone is circulating in the hospital. Hence additional epidemiological studies were clearly warranted in order to increase the insight into the dynamics of MRSA epidemiology in Malaysia. The molecular epidemiology of MRSA isolates were extensively investigated with multiple typing techniques. In this study, molecular characterization of MRSA found that the majority (92.5%) of the isolates belonged to ST-239, spa type t037, and possessed the type III or IIIA SCCmec. Apart from this predominant clone, six (1.5%) isolates of ST-22, with two related spa types (t032 and t4184) and a singleton (t3213), carrying type IVh SCCmec, were detected for the first time in Asia. A limited number of CA-MRSA strains were also detected. These included ST-188/t189 (2.1%), ST-1/t127 (2.3%), and ST-7/t091 (1%). Current results revealed the predominance of ST-239-SCCmec III/IIIA and the penetration of ST-22 with different virulence gene profiles. The emergence in Malaysia of novel clones of known epidemic and pathogenic potential should be taken seriously. In order to trace the source of nosocomial MRSA transmission in the hospital, the impact of HCWs and the hospital environment which could be potential MRSA transmission source were investigated. Of 460 HCWs participants, three (0.65%) were MRSA positive and among the 40 environmental samples four (10%) were found to be MRSA positive. From the current study it is understood that MRSA nasal carriage among HCWs is not the source of infection in the hospital, but hospital environment appears to pose a threat for nosocomial transmission, as all the strains isolated from the environment and clinical cases displayed a similar genetic background. Probably the single most effective way of combating MRSA nosocomial infection is to improve hygiene in hospital environment and healthcare settings, in particular hand hygiene. When MRSA nosocomial infection is confirmed, measures to limit the spread of MRSA include following steps. First, it is necessary to put patients into isolation wards; in one part of a ward, with nursing by designated staff. Secondly, use of single-bedded rooms is highly recommended. Finally, HCWs barrier precautions (gowns, gloves, masks, apron) as physical are barriers to transmission should be implemented. An earlier study carried out in the laboratory has identified the DCM extract of Allium ascalonicum known as Persian shallot, to have surprisingly high antibacterial effect against S. aureus including MRSA with no cytotoxicity at MIC values of 2-4 mg/ml. In order to understand the actual mechanism of inhibition, transcriptome analysis using DNA-Microarray was performed. The investigation revealed that the extract specifically down-regulated the essential microbial fatty acid metabolizing FasII pathway. Because the human serum is full source of fatty acids, it was proven that the A. ascolinicum DCM extract was not suitable for systemic infection. However the result of topical application revealed that although the extract is not suitable for systemic use, it could be potent and safe for topical application. These novel achievements made in this study will be of great value in the modern diagnostic, characterization and treatment. As the molecular system optimized could be readily applied in clinical diagnosis, source tracing assay would be effective in eradication and suppression of FASII through shallot application might be effective in local treatment of MRSA infection. The achievement of the current study is especially a significant contribution to the molecular epidemiology of MRSA in this central teaching hospital for determination of clonal relatedness and emergence of new clones. In addition the routine application of molecular system optimized in this study for the identification and typing of MRSA for epidemiological study definitely contribute toward early diagnosis of MRSA infection in clinical laboratories.